Low-Temperature Combustion of High Octane Fuels in a Gasoline Compression Ignition Engine - Cung, Khanh Duc; Ciatti, Stephen Anthony; Tanov, Slavey; Andersson, Öivind (Frontiers in Mechanical Engineering, 2017)
Gasoline Compression Ignition (GCI) has been shown as one of the advanced combustion concepts that could potentially provide a pathway to achieve cleaner and more efficient combustion engines. Fuel and air in GCI are not fully premixed as compared to homogeneous charge compression ignition (HCCI) which is a completely kinetic-controlled combustion system. Therefore, the combustion phasing can be controlled by the time of injection, usually post injection in a multiple-injection scheme, to mitigate combustion noise. Gasoline usually has longer ignition delay than Diesel. The autoignition quality of gasoline can be indicated by research octane number (RON). Fuels with high octane tend to have more resistance to auto-ignition, hence more time for fuel-air mixing. In this study, three fuels, namely, Aromatic, Alkylate, and E30, with similar RON value of 98 but different hydrocarbon compositions were tested in a multi-cylinder engine under GCI combustion mode. Considerations of EGR, start of injection (SOI), and boost were investigated to study the sensitivity of dilution, local stratification, and reactivity of the charge, respectively, for each fuel. Combustion phasing (location of 50% of fuel mass burned) was kept constant during the experiments. This provides similar thermodynamic conditions to study the effect of fuels on emissions. Emission characteristics at different levels of EGR and lambda were revealed for all fuels with E30 having the lowest filter smoke number (FSN) and was also most sensitive to the change in dilution. Reasonably low combustion noise (< 90 dB) and stable combustion (COV of IMEP < 3%) were maintained during the experiments. The second part of this paper contains visualization of the combustion process obtained from endoscope imaging for each fuel at selected conditions. Soot radiation signal from GCI combustion were strong during late injection, and also more intense at low EGR conditions. Soot/temperature profiles indicated only the high-temperature combustion period, while cylinder pressure-based heat release rate (HRR) showed a two-stage combustion phenomenon.